The impact of market share and banking sector indicators to the profitability of Islamic commercial banks in Indonesia - Rofiatun, Nurul Fatimah (Journal of Islamic Economics Lariba, 2016)
This research has aimed to provide the empirical evidence from the impacts of market share of depositor funds, market share of financing, Total Equity and Size to the profitability (ROA) of Sharia commercial banks in Indonesia. Data used in this paper is secondary data panel with the samples are 4 Sharia commercial banks in Indonesia and in the period of 2010-2015. Data had been analyzed using the data panel regression. According to the result of research, it can be concluded that market share of depositor funds, Total equity and Size have positive and significant impacts to ROA, while the market share of financing has a negative and insignificant relationship to ROA.